ADMINISTRATIVE PROCEDURES FOR HEALTH SERVICES AT THE SOUTH SUWAWA HEALTH CENTER - Susanti Kadir; Frista Iin Wahyuni; Anani, Siske (Jurnal Ilmu Manajemen dan Bisnis, 2024)
Health Admintrasion is a planing , implementation, and service and supervision activity that is responsible for organizing goood helath service development. Healt Service ia an effort to help prepare( take care of) what is needed by pantients who come for treatment at the suwawa selatan healt center. In connection with the flow of healt services, there are still many people who do not understand the rules at the suswawa selatan puskesmas, such as patients who come without a BPJS/KIS treatment guarantee card. With the implementation of existing rules in 2023 until now, people seeking treatment if they do not bring BPJS can Simply show their identity ( KTP). This Research aims at investigating the quality of the Relationship between healt service procedures at the south suwawa healt center so that patient satisfaction in complying with procedures can run with applicable regulations.